The Effect of Dividend Policy and Environmental, Social, and Governance Performance on Company Value - Saksono Budi; Afridayani; Abdullah Mubarok (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2026)
This study aims to obtain empirical evidence on the effect of Dividend Policy and ESG Performance on Company Value. This type of research uses associative quantitative research using secondary data taken from the IDX website and the websites of each company listed on the Indonesia Stock Exchange for the period 2019 to 2023. The sampling method uses purposive sampling using several criteria according to research needs. The samples in this study were 6 companies with a total observation of 30 samples. Hypothesis testing was carried out using the Eviews 12 application. The results of the data analysis showed that simultaneously dividend policy and ESG performance had an effect on company value. While partially it showed that dividend policy had no effect on company value and ESG performance had an effect on company value.